KORUPSI SEBAGAI PENYIMPANGAN KEADILAN SOSIAL DALAM IMPLEMENTASI SILA KELIMA PANCASILA - Wulandari, Yuni; Herlina Eka Putri; Dania Aisyah Putri; Nur 'Aliyuddin; Moch Naufaldi Dzakwan; Kusnul Khotimah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to analyze corruption as a form of deviation from the value of social justice in the implementation of the fifth principle of Pancasila, as well as to examine efforts to eradicate it in government administration. Pancasila is the foundation for Indonesian governance, one of which is the fifth principle, which upholds the value of social justice for all Indonesian people. However, in practice, numerous cases of corruption demonstrate that the government still faces challenges in implementing the value of social justice in the actual state governance. This research design uses a qualitative approach with library research methods through analysis of various relevant literature and research findings. The results indicate that in addition to impacting the national economy, corruption also contributes to social inequality among communities, diminishes public trust in the government, and hinders the equitable distribution of social welfare. Corruption has long been believed to be a concrete form of neglecting the value of social justice, as it involves the abuse of power and state resources for personal or group interests. Several studies have also suggested that factors driving corruption include weakening transparency and state accountability, and unstable law enforcement. In its implementation, the fifth principle of Pancasila requires several supports, such as strengthening the Indonesian legal system, increasing state transparency and accountability, and instilling Pancasila values in the younger generation through character education. Thus, the implementation of the fifth principle of Pancasila is expected to reduce corruption and achieve governance with integrity.